The Art of Chinese Swordsmanship: A Manual of Taiji Jian - Nunberg, Noah (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ansi-language: EN-GB; mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-bidi-font-weight: bold;" lang="EN-GB">Zhang Yun. New York: Weatherhill, 2ª ed. 2005. <span style="mso-ansi-language: FR; mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-bidi-font-weight: bold;" lang="FR">288 pages, 25,4x17,8 cm. I.S.B.N.: 0-8048-3627-2.